2001
DOI: 10.1159/000056092
|View full text |Cite
|
Sign up to set email alerts
|

Antidiarrheal Activity of Wood Creosote: Inhibition of Muscle Contraction and Enterotoxin-Induced Fluid Secretion in Rabbit Small Intestine

Abstract: Wood creosote has long been used as an antidiarrheal agent, but its mechanism of action is not well understood. To elucidate the mechanism of its antidiarrheal activity, we have addressed questions whether it inhibits fluid secretion induced by Escherichia coli heat-stable enterotoxin (STa) in rabbit jejunum in vivo, and whether it inhibits muscle contraction of isolated rabbit ileum ex vivo. Wood creosote (10–100 mg/l) instilled in a ligated loop of jejunum inhibited STa-induced fluid secretion (p < 0.05). It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Although these two pathways are different, the ultimate effects of LT and STa are similar, i.e., activation (opening) of CFTR. Therefore, our previous finding that wood creosote inhibits both LT-and STa-induced fluid secretion of rabbit jejunum in vivo [22,23] strongly suggests that this compound inhibits Cl -secretion from enterocytes by inhibiting a CFTR function.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although these two pathways are different, the ultimate effects of LT and STa are similar, i.e., activation (opening) of CFTR. Therefore, our previous finding that wood creosote inhibits both LT-and STa-induced fluid secretion of rabbit jejunum in vivo [22,23] strongly suggests that this compound inhibits Cl -secretion from enterocytes by inhibiting a CFTR function.…”
Section: Discussionmentioning
confidence: 94%
“…We previously reported its various pharmacological properties [18][19][20][21]. We also reported that intestinal fluid secretion caused by LT and STa enterotoxins of Escherichia coli was inhibited by wood creosote in vivo in rabbit jejunum [22,23]. These results suggest that some constituent of wood creosote inhibits Cl -secretion by affecting cyclic AMP-or cyclic GMP-mediated pathways of Cl -secretion through Cl -channels in intestinal epithelium [9,[24][25][26].…”
Section: Introductionmentioning
confidence: 89%
“…The secretion inhibition was more potent following serosal application whereas in the colon it inhibited STa-induced secretion with equal potency following serosal or mucosal addition. Wood creosote suppressed STa-induced increase in Isc (short circuit current) in a concentration-dependent manner, without causing a complete inhibition [96,97]. STa-induced fluid secretion in ligated rabbit jejunum was also inhibited.…”
Section: Wood Creosotementioning
confidence: 99%
“…tility, slowing intestinal transit time, inhibiting chloride ion secretion, and augmenting net fluid absorption from the intestine in many in vivo and ex vivo animal models. [4][5][6] Clinical experience in humans indicates that wood creosote suppresses intestinal hypermotility and produces an antispasmodic effect in the setting of acute diarrhea. Decreased stool volume and frequency and relief of abdominal cramping have also been observed and reported anecdotally by clinicians.…”
Section: Journal Of Clinical Pharmacology 2003;43:284-290 ©2003 the mentioning
confidence: 99%